ADAPTIVE LOCAL GOVERNANCE DALAM PENGELOLAAN RISIKO BANJIR DI KAWASAN GAMBUT TUMBANG NUSA KALIMANTAN TENGAH - Fitriadi; Richie Fadly; David Bosniari Rajagukguk; Rizki Prihandoko; Neneng Widya Amelia (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This study examines the implementation of adaptive local governance in flood-risk management using a qualitative case-study approach through in-depth interviews, participatory observation, and document analysis involving 28 informants. The findings indicate that adaptive governance in Tumbang Nusa is characterized by Indigenous community participation, multi-stakeholder collaboration, social learning, and institutional flexibility. The novelty of this research lies in the construction of a hybrid governance model that integrates Dayak traditional ecological knowledge-such as the Pali system, Belum Bahadat, and Mamapas Lewu—with modern risk-management systems through mechanisms of knowledge co-production. Key challenges include limited technical capacity, competing interests between economic and ecological actors, and policy inconsistencies across government levels. The theoretical contribution of this study is the enhancement of the adaptive governance concept by embedding local wisdom within the context of tropical peat ecosystems. Strategic recommendations include strengthening local capacity, improving cross-sector coordination, formalizing customary institutions within governance structures, and developing community-based adaptive monitoring systems.